PERSEPSI PEMUSTAKA TERHADAP TRANSFORMASI PERPUSTAKAAN BERBASIS INKLUSI SOSIAL (TPBIS) DI PERPUSTAKAAN DAERAH KABUPATEN PASAMAN - Etisha Alodia; Elva Rahmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe library users’ perceptions of the Social Inclusion-Based Library Transformation (TPBIS) at the Regional Library of Pasaman Regency. The background of this research stems from the community’s limited understanding of the inclusive services provided, as well as the perception that the training programs offered by the library are not relevant to their needs. Additionally, the TPBIS facilities are still underutilized by the public. This research uses a descriptive quantitative approach with a total of 52 respondents. The main instrument used was a questionnaire that had been tested for validity and reliability. The results of the study indicate that library users’ perceptions of TPBIS are categorized as satisfactory, with an average score of 3.50. These findings suggest that the transformation of the library has had a positive impact on community satisfaction and participation. discipline and publisher requirements. Abstracts are typically sectioned logically as an overview of what appears in the paper.